Musculoskeletal system in children and adolescents with inflammatory bowel disease: normal muscle force, decreased trabecular bone mineral density and low prevalence of vertebral fractures - Maratova, Klara; Hradsky, Ondrej; Matyskova, Jana; Copova, Ivana; Soucek, Ondrej; Sumnik, Zdenek; Bronsky, Jiri (European journal of pediatrics, 2017)
UNLABELLED: Low bone mineral density (BMD) and an increased fracture incidence are two extraintestinal complications associated with inflammatory bowel disease (IBD). We aimed to evaluate musculoskeletal traits and assess vertebral fracture (VF) rate in children and adolescents with IBD. Seventy patients with IBD with a median age of 13.8 years were included. The BMD and geometric parameters of the non-dominant tibia were assessed using pQCT. Dynamic muscle functions were evaluated using jumping mechanography. VFs were assessed according to the semiquantitative standardized method by Genant. The muscle functions adjusted for the patients' weight did not differ from the reference population. A low trabecular BMD (Z-score - 1.6; p < 0.001) and cortical thickness (Z-score - 0.7; p < 0.001) were found in children and adolescents with IBD. Conversely, an increased cortical BMD (Z-score 1.1; p < 0.001) was noted. No significant association was found between the 25-OHD serum levels and the bone or muscle measurements. One patient with asymptomatic VF was identified. CONCLUSION: IBD in childhood or adolescents affects bones but not muscles. Bone changes are independent of the 25-OHD serum level. A thoracolumbar spine X-ray should not be routinely recommended in children with IBD. What is Known: • Low bone mineral density and an increased fracture rate are the complications associated with IBD. • Bone strength and structural development is strongly dependent on skeletal muscle stimulation. What is New: • Children with IBD have altered bone density and geometry but normal dynamic muscle functions. • Thoracolumbar spine X-ray should be indicated on an individual basis in children with IBD.
Keywords: svalová síla; logistické modely; Humans; Radiography; trabekulární kostní tkáň; dítě; Absorptiometry, Photon; radiografie; prevalence; Child; Spinal Fractures; Female; rizikové faktory; mladý dospělý; Inflammatory Bowel Diseases; lidé; fraktury páteře; Vitamin D; Muscle functions; Muscle Strength; Mechanography; absorpční fotometrie; idiopatické střevní záněty; ženské pohlaví; Peripheral quantitative computed tomography; Male; Bone strength; Inflammatory bowel disease; Adolescent; Bone Density; kostní denzita; Cross-Sectional Studies; Young Adult; Prevalence; Cancellous Bone; mužské pohlaví; průřezové studie; Logistic Models; mladiství; Risk Factors